Slab mantle dehydrates beneath Kamchatka—Yet recycles water into the deep mantle. (6th August 2016) - Konrad‐Schmolke, Matthias; Halama, Ralf; Manea, Vlad C.
Abstract: The subduction of hydrated slab mantle is the most important and yet weakly constrained factor in the quantification of the Earth's deep geologic water cycle. The most critical unknowns are the initial hydration state and the dehydration behavior of the subducted oceanic mantle. Here we present a combined thermomechanical, thermodynamic, and geochemical model of the Kamchatka subduction zone that indicates significant dehydration of subducted slab mantle beneath Kamchatka. Evidence for the subduction of hydrated oceanic mantle comes from across‐arc trends of boron concentrations and isotopic compositions in arc volcanic rocks. Our thermodynamic‐geochemical models successfully predict the complex geochemical patterns and the spatial distribution of arc volcanoes in Kamchatka assuming the subduction of hydrated oceanic mantle. Our results show that water content and dehydration behavior of the slab mantle beneath Kamchatka can be directly linked to compositional features in arc volcanic rocks. Depending on hydration depth of the slab mantle, our models yield water recycling rates between 1.1 × 10 3 and 7.4 × 10 3 Tg/Ma/km corresponding to values between 0.75 × 10 6 and 5.2 × 10 6 Tg/Ma for the entire Kamchatkan subduction zone. These values are up to one order of magnitude lower than previous estimates for Kamchatka, but clearly show that subducted hydrated slab mantle significantly contributes to the water budget in the Kamchatkan subduction zone. Key Points: Water within the slab mantle beneath Kamchatka are recycled into the deeper mantle Compositional trends in arc volcanics reflect the water content of the dehydrating slab mantle Thermodynamic‐geochemical models can quantify dehydration processes in subducted slabs